2014
DOI: 10.1188/14.cjon.675-680
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes Among Healthcare Providers and Patients Diagnosed With Sickle Cell Disease

Abstract: Sickle cell disease (SCD) is a chronic condition that affects thousands of people worldwide. The purpose of this study is to illustrate some of the challenges and perceptions of people diagnosed with SCD. The aims were to describe stressors, problematic symptoms, sources of support, and interactions with healthcare providers. This descriptive study, using mostly open-ended questions and conceptual analysis, included a sample of patients with SCD who were older than 18 years in ambulatory (57%) and inpatient (4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Self‐care activities are inherent to living with a chronic illness‐ especially when the healthcare system often does not meet expectations as evidenced by negative interactions between individuals with SCD and healthcare providers being common (O'Connor et al . ). Participants in this study reported being negatively perceived by healthcare providers, experiencing poor pain control and receiving inadequate information about treatment options.…”
Section: Discussionmentioning
confidence: 97%
“…Self‐care activities are inherent to living with a chronic illness‐ especially when the healthcare system often does not meet expectations as evidenced by negative interactions between individuals with SCD and healthcare providers being common (O'Connor et al . ). Participants in this study reported being negatively perceived by healthcare providers, experiencing poor pain control and receiving inadequate information about treatment options.…”
Section: Discussionmentioning
confidence: 97%
“…[ 18 ] and other studies also revealed that health-care providers’ views and distrust had an impact on the quality of treatment they provided to patients. [ 19 20 ] Family health-care qualifications were found to have a statistically significant correlation with accurate responses. In order to better care for children with SCD, primary health-care providers must receive more education and training, according to the study findings.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the characteristics of geriatric diseases and the nature of the work, the departmental atmosphere can be relatively depressing and stressful. In addition, some eldercare institution wards are crowded, dirty, and malodorous (O'Connor et al, 2014). Measures should be taken to create healthy and safe work environments for employees, to facilitate successful and sustainable aging-in-workplace.…”
Section: Discussionmentioning
confidence: 99%